2023
DOI: 10.3390/ijms24065904
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Gut Microbes in Benign Prostatic Hyperplasia Model and Finasteride Treatment Model

Abstract: Gut microbes are closely associated with disease onset and improvement. However, the effects of gut microbes on the occurrence, prevention, and treatment of benign prostatic hyperplasia (BPH) are still unclear. We investigated the alteration of gut microbiota with implications for the diagnosis, prevention, and treatment of BPH and identified correlations among various indicators, including hormone indicators, apoptosis markers in BPH, and finasteride treatment models. BPH induction altered the abundance of La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Enhancing the abundance of intestine anxiolytic and antidepressant short-chain fatty acids, Lachnospiraceae was found to be significantly rich in the HA (astaxanthin) treated prostate tumor, indicating a correlation between prostate cancer and microbiota 52 . An 53 found BPH induction altered the abundance of Flavonifractor, but the relationship with prostate cancer requires further study. Consistent with our study, Adlercreutzia was found to have a decreased abundance in the high fat diet mice group, which has been shown to promote prostate carcinogenesis by influencing the gastrointestinal microbiota and microbiota-mediated equol metabolism adversely 54 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Enhancing the abundance of intestine anxiolytic and antidepressant short-chain fatty acids, Lachnospiraceae was found to be significantly rich in the HA (astaxanthin) treated prostate tumor, indicating a correlation between prostate cancer and microbiota 52 . An 53 found BPH induction altered the abundance of Flavonifractor, but the relationship with prostate cancer requires further study. Consistent with our study, Adlercreutzia was found to have a decreased abundance in the high fat diet mice group, which has been shown to promote prostate carcinogenesis by influencing the gastrointestinal microbiota and microbiota-mediated equol metabolism adversely 54 .…”
Section: Discussionmentioning
confidence: 98%
“…Consistent with our study, Clostridiales can convert primary bile acids into toxic secondary bile acids and convert glucocorticoids into androgens by side-chain cleavage, which is likely to contribute to progression of benign prostate hyperplasia 61 . In the study of An 53 , BPH induction altered the abundance of Flavonifractor, and Flavonifractor coule be a potential indicator for the diagnosis of BPH. Although there are limited studies investigating other gut microbiota and prostate or androgen levels, these gut microbiota are mostly found in the correlation of colorectal cancer metabolism, immune function and anti- inflammation 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Enhancing the abundance of intestine anxiolytic and antidepressant short-chain fatty acids, Lachnospiraceae was obseverd to be signi cantly rich in the HA (astaxanthin) treated prostate tumor, indicating correlation between prostate cancer and microbiota (53). An(54) found BPH induction altered the abundance of…”
Section: Discussionmentioning
confidence: 98%
“…Consistent with our study, Clostridiales can convert primary bile acids into toxic secondary bile acids and convert glucocorticoids into androgens by side-chain cleavage, which is likely to contribute to progress of benign prostate hyperplasia (62). In the study of An (54), BPH induction altered the abundance of Flavonifractor, and Flavonifractor coule be a potential indicator for the diagnosis of BPH. Although there are limited studies investigating other gut microbiota and prostate or androgen levels, these gut microbiota are mostly found in the correlation of colorectal cancer metabolism, immune function and anti-in ammation (15).…”
Section: Discussionmentioning
confidence: 99%
“…Among the diets, 5058 exhibited the most distinct effect on beta diversity, while both 5058 and 2920X stood out as the extremes in diet effects on bacterial genera abundance. Although we were unable to measure the phenotypic consequences of these microbial differences, several have predicted pathogenic effects ( Clostridium sensu stricto 1 27 , Ruminococcus 28 , Tuzzerella 29 , Acetatifactor 30 ) while others are predicted to have protective effects on a range of outcomes including gut and metabolic health ( Bifidobacterium 31 , Lactobacillus 32 , Eubacterium nodatum group, Alistipes 33 , Blautia 34 , Eubacterium xylanophilum group 35 ) .…”
Section: Discussionmentioning
confidence: 99%